Whole-Genome Sequence of Lactobacillus acidophilus PNW3, Isolated from Weaned Piglets of the Indigenous South African Windsnyer Pig Breed - Alayande, Kazeem A. (Microbiol Resour Announc, 2019)
A draft genome sequence of Lactobacillus acidophilus PNW3 is reported. The genome assembly is 1,857,655 bp long in 25 contigs with an N(50) value of 230,557 bp and a G+C content of 34.6%. The total number of predicted protein-coding genes is 1,776, with 58 predicted RNAs and 42 predicted pseudogenes.